Comparison of Interleukin-1b-511 C/T Polymorphism in Schizophrenia of Batak and Minangkabau Ethnicities in Pematang Siantar - Wijaya, Raysha Awlia; Fachrial, Edy; Lister, I Nyoman Ehrich; Ariatama, Bayu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
This research is an overview of a comparative study on the Interleukin-1Î²-511 C/T polymorphism in individuals with schizophrenia of Batak and Minangkabau ethnicities in Pematang Siantar, Indonesia. The study aims to investigate genetic differences among these ethnic groups to better understand susceptibility to schizophrenia, which is influenced by multiple factors including genetics. The research uses a comparative categorical analytic approach with a cross-sectional method and involves DNA isolation and polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) examinations. Based on the results,Â significant demographic differences between the Batak and Minangkabau ethnic groups, particularly in gender distribution, age, onset of illness, duration of illness, and PANSS scores. Notably, it finds a significant difference in the occurrence of the C allele and the T allele between the two ethnic groups, with the C allele being more prevalent in the Minangkabau group and the T allele more so in the Batak group. This suggests that the IL-1Î² -511 C/T polymorphism may play a differential role in the susceptibility to schizophrenia among these ethnicities, indicating a potential for ethnic-specific risk factors or protective elements.